Hypertension and grading are important risk factors for occult blood loss in hip arthroplasty: a retrospective study analysis - Song, Erhui; Gao, Feng; Zhang, Guanghe (Frontiers in Surgery, 2026)
ObjectiveTo quantify the impact of hypertension and its grading on occult blood loss (HBL) during total hip arthroplasty (THA) and to offer clinical guidance for minimizing HBL.MethodsBaseline data from femoral neck fracture patients treated with THA between January 2018 and December 2022 were included. SPSS 26.0 statistical software was used for correlation analysis employing statistical methods, including independent samples t-test, Pearson correlation, and multiple linear regression, to identify risk factors for elevated postoperative HBL in THA patients. Hypertension severity was categorized according to international guidelines to investigate the effect of hypertension grading on HBL.ResultsThe mean perioperative bleeding (TBL) among all patients was 1,123.39 ± 518.89 mL, and the mean HBL was 923.93 ± 489.04 mL, which accounted for 78.76% ± 16.09% of the TBL. HBL was significantly higher in hypertensive patients (957.98 ± 509.72 mL vs. 895.94 ± 469.97 mL, P = 0.042). Multiple linear regression analysis revealed that hypertension was an independent predictor of HBL (P = 0.030). Grade 2 hypertension increased HBL by 11.2% (996.46 ± 573.80 mL, P = 0.046), while grade 3 hypertension further increased HBL by 18.7% (1,063.76 ± 584.11 mL, P = 0.044). Hypoalbuminemia had a clinically relevant, but not statistically significant, synergistic effect with hypertension (ΔHBL = 119.60 mL, P = 0.297).ConclusionHypertension ≥ grade 2 (systolic blood pressure ≥ 160 mmHg) independently exacerbates HBL in THA patients through a dose-response relationship. It is recommended that preoperative systolic blood pressure be maintained below 160 mmHg, and metabolic status be optimized to reduce the risk of blood transfusion.